Balancing the multiplicity of different international joint venture (IJV) partners' agendas : IJV directors' contribution to board effectiveness - Petrovic, Jelena (Cranfield University, 2006)
This research examines international joint Venture (IJV) directors' contribution to board effectiveness, utilising a role theoretical framework. The study was prompted by a view that academic debate was limited in its understanding of how directors of IJV boards contribute to board effectiveness whilst balancing the multiplicity of different partners agendas. I particular, the literature review reveals the tendency of the studies of the IJV board director role to describe behaviours that make up a role, at the expense of the actual processes entailed in full filling the role. I addition, the corporate governance (CG) studies have made large inferences from inputs such as board composition to outputs such as board effectiveness, with no direct evidence of the processes that presumably link the inputs to the outputs. Based on the findings from a qualitative exploratory case study of thirteen board directors from three Serbian-foreign joint Ventures based in Serbia, the research proposes _a model that captures the contribution to board effectiveness from a individual IJV board directors perspective. By revealing the actual processes that produce and are affected by IJV board director role outcomes, the study offers a explanation of IJV board director behaviour and opens what has been described as the black box of CG research. The research holds direct implications for role theory, and the IJV and CG literatures. It enhances understanding of IJV board director role, broadens the scope and relevance of role theory beyond the domestic company, extends the study of board director role in the CG literature to IJVs, and contributes to the studies of board dynamics and IJV boards which have been largely under-researched. The research also provides practitioners with a better understanding of the issues and nuances associated with governing of IJVs, as well as knowledge of IJV board director behaviour within the Serbian CG system.